Program Bantuan Pendidikan dalam Peningkatan Akses Pendidikan di Indonesia: Perspektif Keadilan Sosial Islam - Fitri Habiba; Irhamna Irhamna; Ismi Azizatul Khikmah (Tadabbur: Jurnal Integrasi Keilmuan, 2025)
This study aims to analyze education assistance programs and their contribution to improving access to education in Indonesia from the perspective of Islamic social justice. Employing a qualitative approach with a descriptive literature review, the study examines various government education assistance programs, including the School Operational Assistance (Bantuan Operasional Sekolah), the Smart Indonesia Card (Kartu Indonesia Pintar), and the Smart Indonesia Program (Program Indonesia Pintar), as policy instruments designed to expand educational opportunities, particularly for students from economically disadvantaged families. Data were collected from scholarly articles, government reports, books, and other relevant publications and analyzed using thematic content analysis. The findings reveal that these programs have contributed significantly to increasing school participation and reducing financial barriers to education; however, challenges remain regarding equitable distribution, transparency, implementation, and the quality of educational outcomes. From the perspective of Islamic social justice, these programs embody the principles of equity, public welfare (maṣlaḥah), and the state's responsibility to ensure equal educational opportunities for all citizens. The study concludes that education assistance should be evaluated not only based on administrative effectiveness but also on its capacity to promote distributive justice and social welfare in accordance with Islamic values.